The Effects of Academic Giftedness and Gender on Developmental Trajectories of Hopelessness Among Students Living in Economically Disadvantaged Neighborhoods. (October 2019) - Bolland, Anneliese C.; Besnoy, Kevin D.; Tomek, Sara; Bolland, John M.
Although there is much research on adolescent poverty, research related to youth living in communities characterized by extreme poverty who are also identified as academically gifted is lacking. This study explores the development of hopelessness in these youths, compared with peers not identified as gifted, using data from the Mobile Youth and Poverty Study. Specifically, trajectories of hopelessness as a function of gifted status and gender are explored. Results indicate that boys experience greater feelings of hopelessness than girls, regardless of their gifted status, and students identified as gifted have lower levels of hopelessness than their peers not identified as gifted. These latter differences are particularly pronounced during early adolescence (age 10 years) but decline over time and largely disappear by later adolescence (age 18 years). Results suggest that boys may be particularly vulnerable to declining effects of gifted classification as a protector against hopelessness across age and that disadvantaged students who are identified as gifted may benefit from gifted programs that continue at an intense level through their high school years.